Eficiência dos gastos públicos na promoção do desempenho de indicadores do desenvolvimento dos municípios da região Sudoeste do Paraná - Camarotto, Melaine Roberta (2015)
This thesis aims to analyze the public expenditure efficiency as a development promoter. The research focuses on the Southeast region in Parana from 2006 to 2012. As methodological tool, the research used data envelopment analysis (DEA), comprised of 15 study variables (4 inputs and 11 products), product oriented and with constant returns to scale (CRS). The results show that from the 42 municipalities researched, 3 were efficient in the long term analized (7.15%), 32 others obtained weak inefficiency degree and, 7 municipalities showed moderate inefficiency, suggesting that to be 100% efficient, besides offering more products (goods and public services) the municipalities could have decreased expenditures. It's also noticeable that the efficiency does not depend on the amount of financial resources applied, but good practices in management. The management interest areas (Education, Working and Health) concentrate the major volume of allocated resources with the minor waste percentage and, that the proximity of public management and civil society provided by the size of the municipalities favors the efficiency in public expenditure. Thus, while development agent, the State must try to stop the regressive effects (Social inequality; Migration of manpower, capital, goods and services) and provide boosting effects (Infrastructure offering; Education; Health and Work) for development. In a limited resource environment and increasing demand, the inefficiency in public expenditure has shown itself as a limiting factor in development.